Literatur Review Teori Hexagon Dalam Mendeteksi Fraud Pada Laporan Keuangan - Annisa Khairani; Yulia Ribuna Br Bangun; Abel Sonia S; An Suci Azzahra (Jurnal Ekonomi dan Bisnis Digital, 2025)
This article reviews the hexagon theory in detecting fraud in financial statements. This article aims to find out how the results of research in 2025 regarding the hexagon theory in detecting fraud in financial statements? And what are the measurement indicators of the 2025 research results regarding the hexagon theory in detecting fraud in financial statements? The method of writing this scientific article is with qualitative methods and literature review (Library Research). Data obtained from conducting literature studies from various studies on fraud conducted in 2025 from national journals obtained from the Google Scholar page and researchers conducted for all studies in Indonesia. Researchers conducted data searches using the keyword “Hexagon Theory in Detecting Fraud”. The results obtained the most influential factor in detecting fraudulent financial statements is stimulus in 9 articles. Then the next factors are capability in 7 articles, collusion in 6 articles, opportunity in 5 articles, rationalization in 5 articles, and arrogance in 5 articles. The results obtained in the measurement indicators are stimulus with 3 projections, opportunity with 3 projections, rationalization with 2 projections, capability with 1 projection, arrogance with 6 projections, and collusion with 5 projections.